Identification Flavonoid of Bougainvillea spectabilis flowers in Nasiriyah by HPLC and Detection Effect of Extract as Antibacterial - Lafta, Salwa; AL-Waheeb, Alla N. (University of Thi-Qar Journal of Science, 2024)
Many burn wound infections are caused by bacteria such as Staphylococcus aureus, Staphylococcus epidermis, Klebsiella pneumonia, and Pseudomonas aeruginosa, which can be difficult to treat due to antibiotic resistance. As a result, researchers are exploring complementary therapies, such as medicinal plants. In this investigation, a methanolic extract of Bougainvillea spectabilis flowers was prepared using the maceration method at concentrations ranging from 12,5mg/ml to 200mg/ml. Testing was done on the extract separately for antibacterial properties against each of the four bacteria on the Mueller Hinton Agar medium. Results showed that the extract was particularly effective against Gram-positive bacteria, with the greatest effect seen in S. aureus (22.3 mm). The extract was also tested at varying concentrations of 200 %, 100%, 50%, 25%, and 12.5%. HPLC was used to do a qualitative examination of the chemical composition, indicating variety and richness in the chemical constituents in flavonols and phenolic acid. Based on these findings Bougainvillea spectabilis flowers show promise as a source of compounds for clinical usage.